INPS and I-Mutant 2.0: Predicting the Impact of Variations on Apoe Protein Stability - Yaseen, Omar Qahtan; Ulrhman Majeed, Hayder Abd (American Journal of Biomedicine and Pharmacy, 2025)
Cardiovascular diseases are associated with apolipoprotein E (ApoE), a crucial lipid transport protein. APOE gene mutations can have a substantial impact on protein stability, which can alter treatment approaches and disease risk. This study uses I-Mutant 2.0 and INPS, two computational techniques, to assess the effect of 31 single nucleotide variants (SNVs) on ApoE stability. In I-Mutant 2.0, mutations are classified as either destabilizing or stabilizing, while INPS gives numerical ΔΔG values. The findings suggest that 77.4% of mutations result in reduced stability, with the largest destabilizing effects occurring in L38P, W58S, and L72P. G9V and A85V were the most stabilizing mutations, with just 7 mutations (22.6%) projected to increase stability. Even though the two tools have a 71% consistency rate, there are some differences, especially between L38P and R49P, which show how different the computational techniques are. According to the results, stabilizing mutations may offer therapeutic insights, while destabilizing variants may be linked to ApoE malfunction and the advancement of disease. For ApoE-related disorders, future research should combine clinical data, molecular simulations, and experimental validation to improve mutation impact predictions and develop tailored treatment.